Managers' perceptions of modern slavery risk in a UK health-care supply network - Emberson, Caroline Anne; Trautrims, Alexander (2018)
In this paper we argue that, to fully understand managers’ perceptions of modern slavery risk in the context of a UK health-care supply chain, it is necessary to adopt a ‘labour’ supply chain lens that puts the employment relationship at the heart of socially-sustainable supply chain management practice. The distancing and dismantling of employee relations we found, when coupled with an increase in staff turnover, may increase modern slavery risk for permanent, as well as temporary employees, close to the point of commissioning. The implications of this research for policy makers, educators, management practitioners and future research are discussed.